The Effect of Job Satisfaction and Leadership Style on Employee Performance At Pt. Samudera Gemilang Nusantara - Luthfan Tsabit, Muhammad; Ayi Muhyidin (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
Employee performance influenced by various factor crucial in reach success A organization, factors that influence among them satisfaction work, style leadership and performance employees. Goal study This done For know influence satisfaction work and style leadership performance employees at PT Samudera Gemilang Nusantara. The method used in study that is explanatory study with method online survey for data collection and testing hypothesis with Simple Random Sampling technique, and data analysis using device Smart PLS 3.0 software. Research results This indicates that Leadership Style own influence on Employee Performance (β = 0.334, t = 3.023, p < 0.05), so that hypothesis H1 is accepted. In addition that, Satisfaction Jobs are also found have influence on Employee Performance (β = 0.489, t = 5.090, p < 0.05), so that hypothesis H2 is accepted. concluded that satisfaction and style leadership Affecting Employee Performance at PT. Samudera The Glory of the Archipelago.